Parenteral Fish Oil Lipid Emulsions in the Critically Ill: A Systematic Review and Meta-Analysis. (January 2014) - Manzanares, William; Dhaliwal, Rupinder; Jurewitsch, Brian; Stapleton, Renee D.; Jeejeebhoy, Khursheed N.; Heyland, Daren K.
Introduction : ω-3 Polyunsaturated fatty acids contained in fish oils (FO) possess major anti-inflammatory, antioxidant, and immunologic properties that could be beneficial during critical illness. We hypothesized that parenteral FO-containing emulsions may improve clinical outcomes in the critically ill. Methods : We searched computerized databases from 1980–2012. We included randomized controlled trials (RCTs) conducted in critically ill adult patients that evaluated FO-containing emulsions, either in the context of parenteral nutrition (PN) or enteral nutrition (EN). Results : A total of 6 RCTs (n = 390 patients) were included; the mean methodological score of all trials was 10 (range, 6–13). When the results of these studies were aggregated, FO-containing emulsions were associated with a trend toward a reduction in mortality (risk ratio [RR], 0.71; 95% confidence interval [CI], 0.49–1.04; P = .08; heterogeneity I 2 = 0%) and a reduction in the duration of mechanical ventilation (weighted mean difference in days [WMD], −1.41; 95% CI, −3.43 to 0.61; P = .17). However, this strategy had no effect on infections (RR, 0.76; 95% CI, 0.42–1.36; P = .35) and intensive care unit length of stay (WMD, −0.46; 95% CI, −4.87 to 3.95; P = .84, heterogeneity I 2 = 75%). Conclusion : FO-containing lipid emulsions may be able to decrease mortality and ventilation days in the critically ill. However, because of the paucity of clinical data, there is inadequate evidence to recommend the routine use of parenteral FO. Large, rigorously designed RCTs are required to elucidate the efficacy of parenteral FO in the critically ill.